Facilitated adaptation for conservation – Can gene editing save Hawaii's endangered birds from climate driven avian malaria?. (January 2020) - Samuel, Michael D.; Liao, Wei; Atkinson, Carter T.; LaPointe, Dennis A.
Abstract: Avian malaria has played a significant role in causing extinctions, population declines, and limiting the elevational distribution of Hawaiian honeycreepers. Most threatened and endangered honeycreepers only exist in high-elevation forests where the risk of malaria infection is limited. Because Culex mosquito vectors and avian malaria dynamics are strongly influenced by temperature and rainfall, future climate change is predicted to expand malaria infection to high-elevation forests and intensify malaria infection at lower elevations, likely resulting in future extinctions and loss of avian biodiversity in Hawaii. Novel, landscape-level mosquito control strategies are promising, but are logistically challenging and require costly long-term efforts. As an alternative or supplemental strategy, we evaluated the potential of releasing a gene-edited malaria-resistant honeycreeper (Iiwi, Drepanis coccinea ) in Hawaiian rainforests; a strategy known as facilitated adaptation. While this approach also has significant technical challenges and costs, it may offer a more permanent solution to increasing malaria threats. If malaria-resistant honeycreepers can be developed, facilitated adaptation may provide a practical strategy for the reestablishment of abundant avian populations in Hawaiian forests. A successful strategy could be the release of malaria-resistant Iiwi in mid-elevation forests where development of a resistant population has the best chance of success. Establishment of a resistant Iiwi population could provide a source for dispersal and development of resistant populations in high-elevation forests and a permanent source of resistant individuals for translocation to other vulnerable areas.